ANALISIS PENERAPAN PAJAK PERTAMBAHAN NILAI (PPN) PADA PT. LENKO SURYA PERKASA KANTOR PUSAT - Iwan Asmadi; Zahra Zahra; Yosse Hendry; Ratih Agustina (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Abstract The purpose of this study was to examine: Analysis of the Application of Value Added Tax (PPN) at PT. Lenko Surya Perkasa Head Office Jakarta. The researcher used qualitative research methods that aimed to examine and find out the application of Value Added Tax (PPN) in the company. According to Law Number 42 of 2009, Value Added Tax (VAT) is a tax that is imposed on the consumption of goods and services, in a multi-storey customs area in each production and distribution line. From the data obtained from the company, the authors conducted an analysis of the application of Value Added Tax to the company whether it is in accordance with the laws of the taxation. The research method is primary data with data analysis techniques through interviews and observation, documentation and literature study at PT. Lenko Surya Perkasa Head Office Jakarta. The researcher observed for 3 months to find out how the value added tax (PPN) was implemented by the company. Research Results that the company has implemented, calculated, deposited and reported value added tax (VAT) in accordance with applicable regulations.